Gravitational collapse with rotating thin shells and cosmic censorship - Delsate, T.; Rocha, J.; Santarelli, R. (Journal of Physics: Conference Series, 2015)
The study of gravitational collapse is a subject of great importance, both from an astrophysical and a holographic point of view. In this respect, exact solutions can be very helpful but known solutions are very scarce, especially when considering dynamical processes with rotation. We describe a setup in which gravitational collapse of rotating matter shells can be addressed with analytic tools, at the expense of going to higher dimensions and considering equal angular momenta spacetimes. The framework for an exact treatment of the dynamics, relying on a thin shell approximation, is developed. Our analysis allows the inclusion of a non-vanishing cosmological constant. Finally, we discuss applications of this machinery to the construction of stationary solutions describing matter around rotating black holes and to the cosmic censorship conjecture.